Workplace or working environment? Job quality and economic crisis in Spain - Ángel Díaz-Chao; Pilar Ficapal-Cusí; Joan Torrent Sellens (Internet Interdisciplinary Institute, Open University of Catalonia (UOC), 2014)
Through a representative sample of 9,100 and 8,755 employees in 2008 and 2010, and a using structural equation model, this working paper empirically analyses the multi-dimensional determinants (direct effects) of job quality in Spain. The research concludes that: #1 despite the economic crisis, job quality improved over the analysis period; #2 intrinsic job quality, work organisation, and inclusion and access to the labor market are the key explanatory dimensions of job quality; and #3 the main effect of the economic crisis on job quality was a significant restructuring of its explanatory dimensions in favour of those more directly linked to the working environment, and specifically to social relations, health and safety at work, working conditions, and gender equality and work-life balance. These results suggest the importance of the working environment and social relationships, beyond the quality of the workplace, as important tools of employment public policy to improve labor markets and to overcoming the economic crisis.
Keywords: J24; J28; 330; Job quality; Economic crisis; Work organisation; Workplace relationships